Evaluation of the Knowledge Attitude and Practice of Management Skills in Laboratory Set Up among Undergraduate Dental Students - Deepa Viswasini. R1 , Hannah. R2 , Abilasha R3 , Pratibha Ramani4, Gheena S3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Managers in healthcare have a legal and moral obligation to ensure high-quality of patient care. Managementskills can help in influencing the quality and safety of clinical outcomes, processes and performance.Theaim of the study is to analyse the knowledge among undergraduate dental students about the managerialskills in setting up a laboratory so as to assure quality. A cross-sectional observation study was conductedamong undergraduate dental students. A total of 105 participants were included in the study. The study wasconducted online.The data collected were tabulated and analysed. The results showed that 87.6% agreed thatmanagement skills help in the progress of the lab and 77.1% were aware of human resource management. Inour study, 91.4% agreed that high-quality laboratories have better management practises and 88.6% agreedthat leadership is a major management skill. In our study we found that the undergraduate students have lessknowledge and awareness about management skills. This void can be filled by including management skillsand laboratory set up as a part of the curriculum.